Opportunistic Bone Density Measurement on Abdomen and Pelvis Computed Tomography to Predict Fracture Risk in Women Aged 50 to 64 Years Without Osteoporosis Risk Factors. Issue 5 (September 2018) - Fang, Jieming; Franconeri, Andrea; Boos, Johannes; Nimhuircheartaigh, Jennifer; Zhang, Zheng; Brook, Alexander; Brook, Olga R.
Abstract : Objective: The aim of this study is to evaluate opportunistic vertebral bone density measurement in abdominal and pelvic computed tomography (CT) to predict future osteoporotic fracture in women aged 50 to 64 years without known osteoporosis risk factors. Methods: Consecutive female patients 50 to 64 years old without osteoporosis risk factors with 2 CT examinations more than 10 years apart were included. Vertebral height and bone density in each vertebra from T10 to L5 were measured. Vertebral fractures were diagnosed on CT preformed 10 years after the original CT and through online medical records. Results: Thirty (15%) of 199 patients developed osteoporotic fracture. Bone density was lower in patients who developed fractures compared with those who did not ( P < 0.05). Development of osteoporotic fracture of any grade was predicted for patients having bone density less than 180 HU at L4 with sensitivity of 90% (95% confidence interval, 74%–97%) and specificity of 43% (95% confidence interval, 34%–50%). Conclusions: Opportunistic bone density screening can identify women at elevated risk of developing fractures within 10 years.